1991
DOI: 10.1111/j.1365-2141.1991.tb04523.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up of residual disease (MRD) in B lineage acute leukaemias using a simplified PCR strategy: evolution of MRD rather than its detection is correlated with clinical outcome

Abstract: Bone marrow samples of 16 patients (two adults and 14 children) with a B lineage acute lymphoblastic leukaemia (ALL), and in whom Ig heavy chain gene rearrangements were detectable at diagnosis using polymerase chain reaction (PCR), were studied during evolution using PCR. The VDJ junctional fragment of the Ig heavy chain rearranged gene was amplified at diagnosis. After length reduction by restriction digestion, the amplified fragment was recovered by chromatography, labelled using a specific hexamer as a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…25,26 As long as the original rearranged band persisted, which in our hands corresponds to a percentage of at least 1%, no further analysis was performed and contamination was estimated using the value of the peak ( Figure 1). When no signal was observed (corresponding to fewer than 1% malignant cells), a semiquantitative PCR assay was done as described previously [21][22][23] to verify whether MCL cells were still detectable, the sensitivity of the method being 1:10 4 to 1:10 5 ( Figure 2). If residual malignant cells were identified, a LDA, derived from methods described by other authors 27,28 was performed, to better evaluate the number of residual lymphoma cells.…”
Section: Pcr Methodology For Detection Of Residual Malignant Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…25,26 As long as the original rearranged band persisted, which in our hands corresponds to a percentage of at least 1%, no further analysis was performed and contamination was estimated using the value of the peak ( Figure 1). When no signal was observed (corresponding to fewer than 1% malignant cells), a semiquantitative PCR assay was done as described previously [21][22][23] to verify whether MCL cells were still detectable, the sensitivity of the method being 1:10 4 to 1:10 5 ( Figure 2). If residual malignant cells were identified, a LDA, derived from methods described by other authors 27,28 was performed, to better evaluate the number of residual lymphoma cells.…”
Section: Pcr Methodology For Detection Of Residual Malignant Cellsmentioning
confidence: 99%
“…Detection of the IgH rearranged band at diagnosis: The DNA extracted from the original lymph node was amplified using different consensus VH primers: FR1c, 20 FR2c 20 or FR3c 21 and a JH consensus 3′ primer. 21 When amplification could be done with FR3/JH, a probe was directly made according to our previously described method.…”
Section: Pcr Methodology For Detection Of Residual Malignant Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitive and specific assays are needed to improve the detection of minimal residual disease (MRD) and direct the development of strategies for prevention of disease recurrence. Especially in ALL, the polymerase chain reaction (PCR) has been successfully applied to study remission bone marrow samples with high sensitivity (5,16,20,21,31,32). However, some approaches are not practical as performed on a routine basis, and in the vast majority of patients with AML, molecular markers that can be followed…”
mentioning
confidence: 99%
“…With this approach, a detection limit of 5 × 10 −5 was reached in five cases and of 10 −3 in one case, which may not be sensitive enough for clinical application in ALL. 1,5,6,28,29 This problem has also been described in a recent paper by Pongers-Willemse et al, 13 who showed that this type of RQ PCR appeared to be comparable to quantification by dot-blotting but less sensitive than liquid hybridization. An additional disadvantage of this procedure is the expensive and time-consuming need for unique primer and probe sets for each individual patient.…”
Section: Design Of Primers and Probes For Rq Pcrmentioning
confidence: 88%